2023
DOI: 10.1021/acs.biomac.2c01117
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Phosphorus Dendrons Associated with Anti-inflammatory siRNA Reduce Symptoms in Murine Collagen-Induced Arthritis

Abstract: Small interfering RNA (siRNA) holds promise for treating rheumatoid arthritis by inhibiting major cytokines such as tumor necrosis factor-α (TNF-α). We developed original cationic amphiphilic phosphorus dendrons to produce dendriplexes associated with TNF-α siRNA. The dendrons were made of 10 pyrrolidinium end groups and a C17 aliphatic chain. The dendriplexes demonstrated the ability to protect siRNA from nuclease degradation and to promote macrophage uptake. Moreover, they led to potent inhibition of TNF-α e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Studies have shown that phosphorus dendrimers can be used as effective nanocarriers of oligodeoxynucleotides or small interfering RNAs (siRNAs). 46 , 47 As the molar ratio between the positively charged groups of the dendrimer and the phosphate in the siRNA skeleton increases, the surface potential of the cationic phosphorus dendrimer/siRNA complex changes from negative to positive, and the hydrodynamic diameter gradually increases. More importantly, the siRNA molecules in the complex do not change, indicating that cationic phosphorus dendrimers can effectively prevent RNA digestion and can be used as effective nanocarriers for RNA-based disease therapy.…”
Section: Application Of Nanoparticles In the Treatment Of Alimentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that phosphorus dendrimers can be used as effective nanocarriers of oligodeoxynucleotides or small interfering RNAs (siRNAs). 46 , 47 As the molar ratio between the positively charged groups of the dendrimer and the phosphate in the siRNA skeleton increases, the surface potential of the cationic phosphorus dendrimer/siRNA complex changes from negative to positive, and the hydrodynamic diameter gradually increases. More importantly, the siRNA molecules in the complex do not change, indicating that cationic phosphorus dendrimers can effectively prevent RNA digestion and can be used as effective nanocarriers for RNA-based disease therapy.…”
Section: Application Of Nanoparticles In the Treatment Of Alimentioning
confidence: 99%
“…Many nanocarriers have characteristics that are desirable for drug delivery, especially characteristics that improve the solubility, stability, or activity of hydrophobic agents, nucleic acids, enzymes, and peptides. 28 , 47 Some traditional drugs, such as the Src tyrosine kinase inhibitor (PP2) and sivelestat, have disadvantages such as insufficient solubility, poor stability, and short in vivo half-lives, and these disadvantages significantly impact treatment outcomes and lead to suboptimal clinical results. 68 70 The development of nanocarriers effectively overcomes limitations related to drug efficacy and stability, and these nanocarriers allow efficient delivery.…”
Section: Limitations and Prospectsmentioning
confidence: 99%
“…Dendriplexes associated with TNF-a siRNA were synthesized with cationic amphiphilic phosphorus dendrons developed by Yu et al In order to form the dendrons, ten pyrrolidinium end groups were bonded together with an aliphatic chain of C17. As a result of the dendriplexes, siRNA was protected from nuclease-driven degradation, and macrophage uptake was promoted [ 59 ]. To achieve successful mRNA delivery while maintaining a low toxicity profile, Joubert et al modified PAMAM dendrimers with lysine residues as a site-selective anchor.…”
Section: Applications Of Phosphorus Dendrimersmentioning
confidence: 99%